PROBLEM PERNIKAHAN DAN STRATEGI PENYELESAIANNYA: STUDI KASUS PADA PASANGAN SUAMI ISTRI DENGAN USIA PERKAWINAN DI BAWAH SEPULUH TAHUN - Saidiyah, Satih; Julianto, Very (Jurnal Psikologi, 2016)
This study was aimed to explore marriage problems experiencing by couple who had been married for 5-10 years in Yogyakarta and to find out the strategies to solve their problems to be recommended for the counseling section of Ministry of Religious Affair, Indonesia. This study employed qualitative method, particulary case study method. The subjects were 4 couple who had been married for 5-10 years and lived in Yogyakarta. The data was collected using in-depth interview and observation techniques. The data were analyzed using open coding and axial coding. The result of this study showed two initial problems of 5 years marriage: financial prolems and adaptation between marriage couples and extended families. The two strategies to overcome those problems were: building a healthier communication a marriage in the first 5 years, married couples should get stability income and 2) to find the way out to adapt between marriage partners and the whole families. The problems of 6-10years marriage were: the difference between couple in term of parenting style, the decreasing of positive behavior, and the change of communication between couple. The strategies to overcome them were: begin to use positive open communication, including to make agreement about parenting style used in family and repeat the previous positive habits, in which could make greater intimacy and commitments in marriage. The strategies could be used make a warmer and happier marriage.Â